A Semantic Analysis of the Relationship between Fitrah and Education - Ihsan, Nur Hadi; Indallah, Sayyid Muhammad; Shalahudin, Henri (Proceedings of International Conference on Muslim Society and Thought, 2024)
This article is a semantic analysis of the sentence fitrah in the Qur’an. As far as the author reads, the word fitrah is found twenty times with various derivations. The word fitrah has at least the meaning of religion, the command to religion, the creator, and disaster. This article aims to explain the meaning of the sentence fitrah in the Qur’an according to Islamic scholars and thinkers so as to create a complete concept. In analyzing this text, the author uses a descriptive-analytical method to explain the opinions of the scholars; from the etymological meaning of the word so that it becomes a whole concept. The results of this study found that there are at least three important points. First, human nature is religion, namely Islam. Second, human nature is to be a servant and caliph in the world. Third, human nature is the essence of a person; which if done will achieve the purpose for which humans were created or benefit; but if denied will only produce damage or madharat.